Tinjauan Yuridis Eigen Rechting Terhadap Pelaku Tindak Pidana Pencurian (Studi Putusan No. 1867/Pid.B/2020/PN Mks) - Sitti Harlina; Yandi Wahyudi; Jumahir fitra ramadan kahar (Pledoi Law Jurnal, 2024)
ABSTRACT: This research aims to find out how material criminal law is applied to eigen rechting perpetrators. Study the decision